A Multi-Theory Framework for Assessing IoT Adoption in Botswana SMEs - Mphale, Ofaletse; Gorejena, Karikoga Norman; Nojila, Olebogeng (Journal of Information System and Informatics, 2024)
The rapid surge of technological innovation is reshaping industries, and Small and Medium Enterprises (SMEs) are key players in this digital transformation. However, despite their prominence, SMEs often struggle to adopt cutting-edge technologies like the Internet of Things (IoT). While IoT offers the potential to revolutionise SME operations, integrating these interconnected devices presents significant hurdles. Thus, to bridge this research gap, a robust conceptual framework is necessary to understand the factors influencing IoT adoption in SMEs. This study addresses a critical gap by proposing a novel multi-theoretical framework, integrating established technology adoption theories and models like, Diffusion of Innovation (DOI), Technology-Organisation-Environment (TOE) framework, Technology Acceptance Model (TAM), and Unified Theory of Acceptance and Use of Technology (UTAUT). This framework will assist researchers, policymakers, and practitioners in crafting strategies to improve SMEs IoT adoption in Botswana and other developing economies. Future studies will validate this framework through survey research.